2016
DOI: 10.3233/wor-162391
|View full text |Cite
|
Sign up to set email alerts
|

Linking safety climate perception to types of behavior

Abstract: Lower perception toward safety climate was found to be correlated with two groups of DISC's profile. Workers characterized with these two profiles are considered to have priority needs for training or to be assigned to less a hazardous workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Concurrent with the expanded use of DISC assessments around the globe, organizations have increasingly come to rely on behavioral and personality assessments during their employee recruiting, hiring, training, and retention phases (Brundage & Koziel, 2010;McKenna et al, 2002). In academia, studies exploring the benefits of DISC profiling have only occurred in a few areas, such as medical, dental, and nursing training and leadership programs (Corning, 2002;Furlow, 2000;Russell, 1994;Scarbecz, 2007); engineering education (Kim et al, 2008); information systems programs (Pollock, 2009); and workplace safety courses (Sutalaksana & Anatasia, 2016).…”
Section: Disc Assessments and Organizational Efficacymentioning
confidence: 99%
“…Concurrent with the expanded use of DISC assessments around the globe, organizations have increasingly come to rely on behavioral and personality assessments during their employee recruiting, hiring, training, and retention phases (Brundage & Koziel, 2010;McKenna et al, 2002). In academia, studies exploring the benefits of DISC profiling have only occurred in a few areas, such as medical, dental, and nursing training and leadership programs (Corning, 2002;Furlow, 2000;Russell, 1994;Scarbecz, 2007); engineering education (Kim et al, 2008); information systems programs (Pollock, 2009); and workplace safety courses (Sutalaksana & Anatasia, 2016).…”
Section: Disc Assessments and Organizational Efficacymentioning
confidence: 99%
“…Safety climate relates to employees’ perceptions of management’s commitment and performance in regard to safety policy, procedures and practice (Maureen and Arnold, 2010). Safety climate is associated with safety behaviors on the job, worker’s characteristics, working conditions, safety management system and organizational factors (Auyong et al, 2016; Champoux and Brun, 2003; Mullan et al, 2015; Nordlöf et al, 2015; Sørensen et al, 2007; Sutalaksana et al, 2016; Zohar, 2010). Some studies have been conducted to analyze a causal relation between safety-related factors using a structural equation model (Kim et al, 2017; Shin et al, 2018; Snyder et al, 2011; Stave et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the current study focuses on the relationship between respondents' personality dimensions and their accident experiences. The Extraversion dimension in BFI appears to be comparable with talkative (I), assertive (D), outgoing (I), outspoken (D), dominant (D), forceful (D), enthusiastic (I), sociable (I), and adventurous (D) traits in DISC behavior type [9]. Based on our previous study, (I) the public self was negatively related to workers' safety commitment and their perceptions toward safety climate.…”
Section: Resultsmentioning
confidence: 83%
“…On our previous work using Marston's tetra-logy of behavior type, referring to the DISC (Dominance, Influence, Steadiness, and Conscientiousness) traits, we found an association between the Conscientiousness trait in public self and accident involvement, though the correlation was low [8]. Furthermore, we found that the Influence trait in public self on DISC has a correlation with lower perception toward safety climate [9]. The challenge of using the DISC is that each DISC trait may vary to direct the behaviors shown by an individual in public self, private self, and perceived self [8].…”
Section: Introductionmentioning
confidence: 64%